1985
DOI: 10.1128/mcb.5.4.595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alterations in cellular iron on biosynthesis of the transferrin receptor in K562 cells.

Abstract: Treatment of K562 cells, a human erythroleukemia cell line, with desferrioxamine raised the levels of the receptor for transferrin (Tf) two-to threefold over that of the control cells. The levels of receptor were reduced by at least 50 and 35% of that of the control in cells treated with diferric Tf and ferric ammonium citrate, respectively. These changes were of total cellular receptors with no alteration in the proportion of receptors found on the cell surface. The half-lives of the receptor were identical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 12 publications
(7 reference statements)
4
47
0
Order By: Relevance
“…TfR1 expression is ubiquitous, consistent with its role in cellular iron delivery. The stability of TfR1 mRNA is negatively regulated by intracellular iron levels through iron-responsive elements (IREs) in the 3Ј untranslated region (Mattia et al, 1984;Ward et al, 1984;Rao et al, 1985;Sciot et al, 1987;Owen and Kuhn, 1987;Casey et al, 1988;Mullner and Kuhn, 1988;Lu et al, 1989;Mullner et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TfR1 expression is ubiquitous, consistent with its role in cellular iron delivery. The stability of TfR1 mRNA is negatively regulated by intracellular iron levels through iron-responsive elements (IREs) in the 3Ј untranslated region (Mattia et al, 1984;Ward et al, 1984;Rao et al, 1985;Sciot et al, 1987;Owen and Kuhn, 1987;Casey et al, 1988;Mullner and Kuhn, 1988;Lu et al, 1989;Mullner et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…TfR1 expression is ubiquitous, consistent with its role in cellular iron delivery. The stability of TfR1 mRNA is negatively regulated by intracellular iron levels through iron-responsive elements (IREs) in the 3Ј untranslated region (Mattia et al, 1984;Ward et al, 1984;Rao et al, 1985;Sciot et al, 1987;Owen and Kuhn, 1987;Casey et al, 1988;Mullner and Kuhn, 1988;Lu et al, 1989;Mullner et al, 1989).TfR2 differs from TfR1 in notable ways. TfR2 binds Tf in a pH-dependent manner, but its affinity for Fe 2 Tf (K D ϳ30 nM; Kawabata et al, 2000;West et al, 2000) is significantly lower than that of TfR1 (K D ϳ1 nM, Tsunoo and Sussman, 1983;Enns et al, 1991;Richardson and Ponka, 1997).…”
mentioning
confidence: 99%
“…The receptor-Tf complex is internalized by a process of receptor-mediated endocytosis in which the iron is dissociated from the Tf (3). Investigators have previously shown that the levels of intracellular iron regulate the level of expression of the Tf receptor (6, 8,9,14). Raising the levels of intracellular iron by treatment of K562 cells (a human erythroleukemic cell line) with either human diferric Tf or ferric ammonium citrate results in decreased levels of the receptor.…”
mentioning
confidence: 99%
“…These changes in cellular content of the Tf receptor through manipulation of intracellular iron levels are caused by altered rates of biosynthesis of the receptor. Corresponding changes in the levels of translatable mRNA for the receptor were measured by in vitro translation (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation